The labyrinth of doom - Gibbs, Stuart, 1969- (Gibbs, Stuart, 1969- Once upon a Tim series, 2022)
"Prince Ruprecht is very upset that knights-in-training Tim and Belinda have thwarted his plans and ruined his chances with Princess Grace. So to get even, he has kidnapped the princess and trapped her in the most complicated, dangerous, complex, dastardly, biggest (okay, you get the point) ... and scariest maze in all the world! Now it's up to Tim, Belinda, Ferkle, and Rover to fend off menacing beasts (like the minotaur), conquer treacherous obstacles (like chasms filled with cave sharks), find their way through the labyrinth (which is very tricky), and rescue the princess before time runs out. Oh, and also, they need to remember how to get back out again ... or they'll be trapped inside the maze forever"--